PENGARUH KERJASAMA STAKEHOLDERS TERHADAP KESIAPSIAGAAN DALAM MENGHADAPI KEBAKARAN DI UNIT SATUAN KERJA PRESERVASI JEMBATAN X KOTA SURABAYA - Nurriwanti, Nabylla Sharfina Sekar; Kartika, Ayu Prima (Jurnal Kesehatan Lentera 'Aisyiyah, 2024)
Fire incidents in the workplace is something that is undesirable because it can cause suffering and loss to the agency and workers. Preparedness is important in protecting property and saving lives when a fire occurs. Based on the construction safety plan document at the Surabaya City Bridge X Toll Road Preservation Work Unit, there is a high risk of fire. This study is an analytical observational study with a cross-sectional time approach. The sample in this study was 44 emergency response team respondents. The variables used are stakeholder collaboration and preparedness in dealing with fires using binary logistic regression analysis to see the influence between variables. This research was conducted at the Surabaya City Bridge X Toll Road Preservation Work Unit. The results of the study showed that 59.1% of emergency response teams said that stakeholder collaboration had been going well. From this study, it is concluded that there is a significant influence of stakeholder collaboration on preparedness in dealing with fires in the Surabaya City Bridge X Toll Road Preservation Work Unit with a p-value of 0.011.